Influence of temperature on the behavior of DGEBA (bisphenol A diglycidyl ether) epoxy adhesive. (April 2015) - Reis, J.M.L.; Amorim, F.C.; da Silva, A.H.M.F.T.; da Costa Mattos, H.S.
Abstract: In this work, the behavior of a diglycidyl ether of bisphenol A (DGEBA) was studied. Tensile tests were conducted under a wide range of temperatures (from 25 °C to 130 °C). It is observed that temperature has a great influence on the mechanical response of PolyAnchor 4100 HTP adhesive. In particular, both stiffness and ultimate tensile strength decrease with increasing temperature. Also, it is proposed a one-dimensional viscoelastic phenomenological model, able to yield a physically realistic description of temperature sensitivity and damage observed in tensile tests. Just two tests performed at different constant temperatures are needed to fully identify the material parameters that appear in the model. The experimental results are presented and compared to model estimations of damage progression and show good agreement.